Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Lindeque, Penelope K.; Hann, Isabelle; Parry, Helen E.; Cook, Kathryn B.; Lindley, Anthony J. W.; Mayor, Daniel J. (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis, accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus-dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.